PENGARUH PENDAPATAN ASLI DAERAH, BELANJA MODAL DAN UKURAN PEMERINTAH DAERAH TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH DI PROVINSI JAWA TENGAH - Meutia, Windari (Universitas Slamet Riyadi, 2021)
Abstract ThisZ study aims to determine Zthe effect of local revenue, Zcapital expenditure and size of local Zgovernment on the financial Zperformance of Zlocal governments in Central Java province. This research was conducted in Central Java Province, the type of data used is quantitative zdata. The zdata source zused is zsecondary data. The zdata used zin zthis study were obtained from information on the APBD, the realization of the APBD and the balance zsheets zof the zdistrict zand municipal zgovernments zof Central zJava Province during the z2016-2018 zfiscal zyear with zthe zsampling population using purposive sampling. The zpopulation in this study is the Regional Government of Central Java Province,z amounting zto 35 regions zconsisting of 29 zdistricts zand z6 cities. The zsamples in zthis study zwere all zdistricts and zcities of zCentral zJava zProvince zwhose data met the requirements zand could zbe obtained zfrom the zDirectorate General zof zFiscal zBalance, Ministry zof zFinance. The zresults zof zthis study indicate zthat local revenue has a significant zeffect zon the zfinancial zperformance of local zgovernments. Capital expenditures zdo not zhave a significant zeffect on zlocal government zfinancial performance. The size zof thez local government zhas a zsignificant zeffect on zthe financial zperformance of zthe zlocal zgovernment. Keywords: PAD, capital expenditure, size, financial performance